Functional characterization of a cell wall invertase inhibitor StInvInh1 revealed its involvement in potato microtuber size in vitro - Liu, Cheng; Hu, Shuting; Liu, Shuyi; Shi, Weiling; Xie, Debin; Chen, Qi; Sun, Hui; Song, Linjing; Li, Ziyu; Jiang, Rui; Lv, Dianqiu; Wang, Jichun; et al. (Frontiers in Plant Science, 2022)
Cell wall invertase (CWI) is as an essential coordinator in carbohydrate partitioning and sink strength determination, thereby playing key roles in plant development. Emerging evidence revealed that the subtle regulation of CWI activity considerably depends on the post-translational mechanism by their inhibitors (INHs). In our previous research, two putative INHs (StInvInh1 and StInvInh3) were expected as targets of CWI in potato (Solanum tubersum), a model species of tuberous plants. Here, transcript analysis revealed that StInvInh1 showed an overall higher expression than StInhInh3 in all tested organs. Then, StInvInh1 was further selected to study. In accordance with this, the activity of StInvInh1 promoter increased with the development of leaves in plantlets but decreased with the development of microtubers in vitro and mainly appeared in vascular bundle. The recombinant protein StInvInh1 displayed inhibitory activities on the extracted CWI in vitro and StInvInh1 interacted with a CWI StcwINV2 in vivo by bimolecular fluorescence complementation. Furthermore, silencing StInvInh1 in potato dramatically increased the CWI activity without changing activities of vacuolar and cytoplasmic invertase, indicating that StInvInh1 functions as a typical INH of CWI. Releasing CWI activity in StInvInh1 RNA interference transgenic potato led to improvements in potato microtuber size in coordination with higher accumulations of dry matter in vitro. Taken together, these findings demonstrate that StInvInh1 encodes an INH of CWI and regulates the microtuber development process through fine-tuning apoplastic sucrose metabolism, which may provide new insights into tuber development.